DESKRIPSI PEMBELAJARAN SAINS DALAM KEGIATAN EKSPLORASI DI HALAMAN SEKOLAH UNTUK ANAK USIA 5-6 TAHUN - Ratni Oktaviyani Luly; Nunung Suryana Jamin; Rapi Us Djuko; Waode Eti Hardiyanti (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2021)
The purpose of this study was to determine the learning of science in exploratory activities in the school yard for children aged 5-6 years. The research method used in this research is descriptive qualitative with a sample of 15 children, consisting of 9 boys and 6 girls. Data collection techniques used in the form of observation, interviews, and documentation. The data analysis technique used is the interactive model by Miles & Hubberman. The results showed that children's science learning in exploration activities in the school yard for children 5-6 years old at Kartini Kindergarten, Mopusi Village, Lolayan District, Bolaang Mongondow Regency had developed optimally, referring to 3 (three) indicators that were met, namely planning and regulation, plans for security, and a positive attitude that must be built towards scientific activities.